2010
DOI: 10.1186/1471-2407-10-686
|View full text |Cite
|
Sign up to set email alerts
|

Expression of BMI-1 and Mel-18 in breast tissue - a diagnostic marker in patients with breast cancer

Abstract: BackgroundPolycomb Group (PcG) proteins are epigenetic silencers involved in maintaining cellular identity, and their deregulation can result in cancer. Expression of Mel-18 and Bmi-1 has been studied in tumor tissue, but not in adjacent non-cancerous breast epithelium. Our study compares the expression of the two genes in normal breast epithelium of cancer patients and relates it to the level of expression in the corresponding tumors as well as in breast epithelium of healthy women.MethodsA total of 79 tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…In view of the low expression of Ezh2 in normal resting populations, selective pharmacological intervention to inhibit Ezh2 activity in both wild type and mutant lymphomas is a promising approach that warrants further research. Mel-18 expression was previously reported in several normal adult tissues [15][16][17]. In RLH, we found that few cells expressed Mel-18 with moderate intensity while some populations expressed…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In view of the low expression of Ezh2 in normal resting populations, selective pharmacological intervention to inhibit Ezh2 activity in both wild type and mutant lymphomas is a promising approach that warrants further research. Mel-18 expression was previously reported in several normal adult tissues [15][16][17]. In RLH, we found that few cells expressed Mel-18 with moderate intensity while some populations expressed…”
Section: Discussionsupporting
confidence: 79%
“…The upregulation of Bmi-1 was reported in a variety of cancers, and sometimes correlated with a poor prognosis [6,[12][13][14]. Mel-18/PCGF2 is a component of the PRC1.2 complex, and was previously described as a tumor suppressor that is expressed in the normal state and suppressed in neoplastic conditions in gastric, prostate and breast cancers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…of ----------------------------------Clinicopathological patients, HSP90- Immunohistochemical analysis. IHC was performed on 5-µm-thick sections from formalin-fixed, paraffin-embedded tissue samples applied to coated slides, as described in a previous study (16). The following antibodies were used together with a streptavidin-peroxidase (SP) conjugate (SP-IHC method): HSP90 (ab13492; 1:150) and HIF-1α (ab85886; 1:200) (both from Abcam, Cambridge, MA, USA).…”
Section: Totalmentioning
confidence: 99%
“…Previous studies, including our own, have demonstrated that MEL-18 expression is lower in human breast cancer tissues than in normal breast tissues (9,10,14), but the clinical importance of MEL-18 in different breast cancer subtypes has not been evaluated. In this study, based on IHC analysis of breast cancer specimens and the gene expression profiles of multiple independent microarray datasets from various breast cancer cohorts, we demonstrated a negative correlation of MEL-18 Therefore, these data indicate the importance of MEL-18-mediated SENP1 regulation in breast cancer progression and suggest SENP1 and MEL-18 as markers of ER-α negativity.…”
Section: 0mentioning
confidence: 99%
“…Although further clinical evidence is needed, accumulating studies have suggested that MEL-18 acts as a tumor suppressor in several human tumors, including breast cancer (7)(8)(9)(10)(11). Our previous studies have also revealed that MEL-18 loss facilitates stem cell activity, cell growth, angiogenesis, and epithelial-mesenchymal transition (EMT) in breast cancer (12)(13)(14)(15), implying an association of MEL-18 loss with an aggressive phenotype.…”
Section: Introductionmentioning
confidence: 99%